MACHINES MAINTENANCE MANAGEMENT PRACTICES IN SAWMILL INDUSTRIES IN NIGER STATE, NIGERIA - Yisa, Emmanuel; Okwori, Ogbanje Robert; Hassan, Muhammad Abdullahi (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
The frequent breakdown of machine which usually affect the production and the abandoning of machines that have not exhausted their life span become serious consigned. Hence, the study was carried out to identified machines maintenance management practices in sawmill industries in Niger State, Nigeria. A descriptive survey research design was employed for the study. The total of 88 respondents comprising of 22 managers, 44 machine operators and 22 saw doctors of sawmill industries of Niger State were used as population of the study. A structure questionnaire was developed by the researcher and used for data collection. The instrument was face validated by two lecturers from the Department of Industrial and Technology Education, Federal University of Technology Minna and one sawmill manager. The instrument was tried-out on 17 sawmill workers of Jebba South Kwara State. The reliability coefficient of the instrument was 0.86. Mean and standard deviation were used as the statistical tools to analyze the data, while Analysis of Variance (ANOVA) was employed to test hypotheses of the study at 0.05 level of significant. Based on the data collected and analyzed, the following findings were made. The machines maintenance coordinating and evaluating are moderately practiced in sawmill industries in Niger State. Based on the findings, the following recommendations were made: Government and sawmill owners should organized seminars and training for their workers to improve on management of maintenances activities in sawmill industries.